Nowe obserwacje wilków Canis lupus w rejonie Warszawy - Gryz, Jakub; Jackowiak, Mateusz; Jasińska, Karolina; Krauze-Gryz, Dagny (Leśne Prace Badawcze, 2025)
Regular sightings of grey wolves have been reported from Warsaw in media in recent years. Therefore, we used our empirical material collected during an intensive study focusing on urban fauna (2015–2024) to list all recorded observations of the species. The methods included photo-trap monitoring of green areas (121 locations) and winter snow tracking along transects (over 830 km). In addition, from April to September 2024, camera traps were set up at the nearby Rembertów military training area on the eastern border of Warsaw. In Warsaw, a wolf was registered only once in the Kabaty Woods (16.04.2021). To our knowledge, the wolf’s presence in the city was accidental. In the Rembertów military area, the presence of wolf packs was probably permanent. Cameras photographed wolves there three times within six months period (9.04, 29.06, and 31.07. 2024).